Reading to learn : lessons from exemplary fourth-grade classrooms - Allington, Richard L.; Johnston, Peter H. (New York : Guilford Press, 2002)
After reviewing current research on upper-elementary reading instruction, the book takes readers directly into the classrooms of six highly successful teachers. Like the previously published Learning to Read, which focused on the first grade, Reading to Learn offers a rare view of the techniques and strategies good teachers use to engage students, help them develop as thoughtful readers and writers, and bolster self-directed learning and literate conversation. Bringing to life the complexities of day-to-day work with diverse students, the book provides inspiration and practical ideas for any teacher in the upper-elementary grades.
What do we know and need to know about good fourth- grade teaching? Teaching fourth grade in the 21st Century -- What do we know about effective fourth-grade teachers? -- What do good classrooms look and feel like? Inquiry and a good conversation: "I learn a lot from them" / Peter H. Johnston, Joan Backer -- "Responsibility and respect for themselves and for whatever it is they're doing": learning to be literate in an inclusive classroom / Gay Ivey -- "Focus on the real and make sure it connects to kids' lives" / Ruth Wharton-McDonald, June Williamson -- "We learn from each other": collaboration and community in a bilingual classroom / Jeni Pollack Day -- A caring, responsible learning community / Peter H. Johnston, Mary Ellen Quinlan -- "I want students who are thinkers" / Peter H. Johnston, Tracey Bennett, John Cronin -- Whar have we leatned about good fourth-grade teaching? Integrated instruction in exemplary fourth-grade classrooms -- Literate achievements in fourth grade -- The nature of good fourth-grade teaching -- Shifting the focus of the reading debate: a cautionary afterword / Gerald G. Duffy -- Appendix: Achievement growth on standardized reading tests.
Includes bibliographical references (p. 235-248) and index.
Keywords: Reading (Elementary) -- United States -- Case studies; Fourth grade (Education) -- United States -- Case studies; Lecture (Enseignement primaire) -- v; z